Implementasi Metode Waterfall untuk Laporan Petugas Lapangan Berbasis Web - Sitio, Sartika Lina Mulani; Sariadi, Slamet (LPPM UNIKA Santo Thomas, 2023)
Indonesia Maritime Education and Logistics is a subsidiary of PT. Indonesian Harbor (Persero). This PT provides training, assessment and consulting services in the fields of ports, shipping, logistics and management. Improving the quality, profits and progress of the company is one of the programs implemented by PT. Indonesian Maritime and Logistics Education. Usually superiors such as SPV and DVP find it difficult to receive reports from field officers because they still report their work activities using manual forms, namely using paper as the report they receive from officers and officers must also attach before and after work photos taken within one month. and this often means that files on the cellphone are lost due to accidentally deleting files or updating the cellphone. The waterfall method is a system development method used because this method provides a sequential or ordered software life flow approach starting from analysis, design, coding, testing and support stages. With this web-based field officer reporting application, the officer reporting process becomes better because all reporting from start to finish is computerized and this also makes it easier for superiors to mentor the work of field officers which can be seen from the report results in the reporting system. by every officer.